The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1177/0956797614538458
|View full text |Cite
|
Sign up to set email alerts
|

Young Children Bet on Their Numerical Skills

Abstract: Metacognition, the ability to assess one’s own knowledge, has been targeted as a critical learning mechanism in mathematics education. Yet, the early childhood origins of metacognition have proven difficult to study. Using a novel nonverbal task and a comprehensive set of metacognitive measures, we provide the strongest evidence to date that young children are metacognitive. We show that children as young as 5 years make metacognitive “bets” on their numerical discriminations in a wagering task. However, contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 48 publications
5
61
0
Order By: Relevance
“…Our findings are in line with theoretical frameworks proposing that metacognitive sensitivity stems from simple evaluations of the quality of internal representations [1, 6, 7, 8]. These rudimentary neural computations could in principle already be present in the infant brain [33]. One possibility is thus that metacognitive operations are computed automatically as soon as infants start making decisions.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our findings are in line with theoretical frameworks proposing that metacognitive sensitivity stems from simple evaluations of the quality of internal representations [1, 6, 7, 8]. These rudimentary neural computations could in principle already be present in the infant brain [33]. One possibility is thus that metacognitive operations are computed automatically as soon as infants start making decisions.…”
Section: Discussionsupporting
confidence: 88%
“…Yet verbally reporting one’s own mental states involves more than pure metacognitive monitoring [34, 35]. Consistent with this idea, metacognition has been found to involve both explicit and implicit processing modes in adults [15, 34, 35, 36], and a few recent studies found that children can pass metacognitive tasks at younger ages when no verbal report is required [31, 33, 37]. In particular, we found that 20-month-old infants are able to ask for help non-verbally in order to avoid making errors [37].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Future research could test this possibility by investigating the influence of ANS confidence hysteresis on children’s error patterns in symbolic math problems. Another possibility is that ANS precision plays no direct or supporting role as children attempt to solve math problems, but rather that children experience a sense of self-efficacy that is specific to the mathematical domain (Hackett & Betz, 1989; Vo, Li, Kornell, Pouget, & Cantlon, 2014). That is, ANS confidence hysteresis might affect children’s internal sense of their ability to reason about quantities.…”
Section: Discussionmentioning
confidence: 99%
“…Metacognitive knowledge (Özsoy, 2011;Schneider & Artelt, 2010) and cognitive regulation (Morosanova, Fomina, Kovas, & Bogdanova, 2016) are both associated with higher levels of mathematical achievement. Numerical metacognitive knowledge in young children (aged five) can predict levels of mathematical knowledge at school (Vo, Li, Kornell, Pouget, & Cantlon, 2014). Metacognitive beliefs and monitoring are also associated with mathematical problem-solving performance in primary school students (Cornoldi, Carretti, Drusi, & Tencati, 2015).…”
Section: Introductionmentioning
confidence: 99%